Lilis Lismaya - Lilis Lismaya; Putut Marwoto; Sunyoto Eko Nugroho (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to reduce household organic waste through the use of organic waste as a natural detector of formaldehyde content in food snacks. The organic waste used in this study was red garlic skins, dragon fruit skins and purple sweet potato skins. This research is an experimental research. The stages of the research started with the extraction of anthocyanins from the three organic wastes, direct detection of formalin and detection of food ingredients. The formalin concentrations tested were 0.5%, 1%, 2%, 5% and 25%. Detection ability can be seen from the color change between control and formalin treatment. Garlic skin produces a red extract, dragon fruit skin produces an orange extract, and purple sweet potato skin produces a deep red extract. Test results on 20 samples of food snacks around the campus using the three organic waste extracts proved that all samples contained formaldehyde in varying concentrations. The highest 50% formalin content was found in yellow noodles and meatballs. The conclusion is that purple beetle skin, dragonfruit skin, and red garlic skin can be used as natural detectors for formalin in campus snacks.